The Study of Indisch Architecture Development as an Effort in Preserving the Heritage of Colonial History in Medan - Imam Faisal; Hajar Suwantoro (Budapest International Research and Critics University, 2019)
The development of this nation's history does not separate from the development of colonial architecture. It is necessary for fundamental knowledge so that the understanding of the development of architecture can be part of the nation's history that is important to be studied. One of the important things from architectural development in Indonesia is the coming of Dutch influence. The term of Indisch is used to refer to the developing architecture in the colonial area. The development of this architecture extends mainly at major cities in Indonesia including Medan City. This paper describes the development of Indisch architecture in Medan City and the efforts to maintain and preserve it. The method used is a descriptive qualitative approach in order to describe the facts that exist in the field and to study it by the theory used. The result shows that the development of architecture does not separate from the development of the city in the colonial period. By growing of city development during the colonial era, so the building is an important element in it. The conservation effort is an attempt to maintain the existing history and memory.